O paraíso extraviado: elementos neo-utópicos e distópicos em Pessach, A travessia, A festa e A terceira margem - Sarmento-Pantoja, Tânia Maria Pereira [UNESP] (2005)
This research is essentially based on the idea that every object of culture is also an object of barbarism, as Walter Benjamin thinks. In this way, the analyzed corpus, composed by the novels Pessach, a Travessia, A Festa and A Terceira Margem, are understood as narratives that testify permanent violations, expressed in various forms, in addition to dialoguing intertextually with historical references marked by violence, especially violence resulting from repression produced by the exception state. The governability of the state of exception and its repressive character is an important formulation for the understanding of the narrative economy of the three novels analyzed. These novels are also profoundly marked by a change in experience with time itself and thus in the aesthetic dimension: in working with representation. This aesthetic dimension accompanies the broad dislocations of the utopian energies that compose them. Energies that decompose or progress to dystopian and / or neo-utopian energies. In considering these aspects we raise the following thesis: if dystopia is an important narrative element with narratological and also aesthetic function of emphasizing the violation, due to an authoritarian regime of governability, which is present in the three narratives, based on the dialogue intertextual with historiography and with the culture related to the state of exception, how the integration of the dystopic elements – and, on the contrary, the utopian elements – penetrate the transformations undergone by the post-dictatorial Brazilian novel? In order to demonstrate this thesis we produced a corpus analysis, based on a case study, in association with investigations carried out by historians, especially those elaborated by Marcelo Ridenti (2000) and Carlos Fico (1997; 2004) with theories about utopia, dystopia and neo-utopia; and with the corpus of studies of literary criticism on Brazilian fiction, which questioned the state of exception established in Brazil between the 60s and 80s of the 20th century.